The correlation between the developmental stages of pea microspores and the morphology of flower buds - Li, Zelin; Tang, Yuan; Chen, Shengrong; Yang, Yuheng; Zhang, Yujuan; Xiao, Li; Feng, Xiao; Wang, Mei (BIO web of conferences, 2024)
To investigate the correlation between microspore development stage and the appearance and morphology of flower organs in Pisum sativum, the novel pea materials YP58 and YW90 were employed as experimental subjects. Flower buds exhibiting varying diametral ranges were chosen for cytological examination, and the saffron solid green staining method was employed to discern the diverse developmental stages and morphological attributes of microspores. Furthermore, the association between flower bud size and microspore development stage was examined. The findings revealed that the microspore development in both pea materials predominantly encompassed the microspore mother cell stage, tetrad stage, early and middle mononuclear stage and late mononuclear stage, each displaying distinct features. Notably, the development duration of microspores exhibited a close correlation with the longitudinal diameter of the flower bud. The correlation between microspore development progression and the longitudinal diameter of the flower bud was consistent in both pea materials. Therefore, the longitudinal diameter of the flower bud can serve as a primary indicator for assessing the microspore development stage.